Two new Begonia species (Begoniaceae) and notes on extended distribution ofBegonia calcarea Ridl. from Sarawak, Borneo - Tawan, C.S; Ipor, I.B.; Hidir, M.; Ampeng, A.; Marzuki, B.; Meekiong, K. (Folia malaysiana, 2009)
Two new begonias from Sarawak are described and illustrated. Begonia hidiri Tawan, Ipor & Meekiong is a new species collected and recorded from Mount Murud areas. This hairy cane-like begonia belongs to Section Petermannia recorded at altitude more than 1600 1700 meters above sea level which occupied the damp and wet places of submontane mixed dipterocarp forests. Begonia kurakura Tawan, Ipor & Meekiong is a dwarf begonia from virgin hill mixed dipterocarp forest at 130 -140 meters altitude collected and recorded from Lanjak Entimau Wildlife Sanctuary. This beautiful species also belongs to section Diploclinium. Notes on extended distribution ofB. calcarea Rid!. are also included.